Indigenous microbial community governs the survival of Escherichia coli O157:H7 in constructed wetlands. (15th May 2023) - Zhang, Nan; Liang, Chunling; Kan, Peiying; Yangyao, Jiannan; Lu, Dingnan; Yao, Zhiyuan; Gan, Huihui; Zhu, David Z.
Abstract: The survival pattern of Escherichia coli O157:H7 ( E. coli O157:H7) and its regulatory factors in natural environments have been widely studied. However, there is little information about the survival of E. coli O157:H7 in artificial environments, especially in wastewater treatment facilities. In this study, a contamination experiment was performed to explore the survival pattern of E. coli O157:H7 and its central control factors in two constructed wetlands (CWs) under different hydraulic loading rates (HLRs). The results showed that the survival time of E. coli O157:H7 was longer in the CW under the higher HLR. Substrate ammonium nitrogen and available phosphorus were the main factors that influenced the survival of E. coli O157:H7 in CWs. Despite the minimal effect of microbial α-diversity, some keystone taxa, such as Aeromonas, Selenomonas, and Paramecium, governed the survival of E. coli O157:H7. In addition, the prokaryotic community had a more significant impact on the survival of E. coli O157:H7 than the eukaryotic community. The biotic properties had a more substantial direct power on the survival of E. coli O157:H7 than the abiotic factors in CWs. Collectively, this study comprehensively disclosed the survival pattern of E. coli O157:H7 in CWs, which is an essential addition to the environmental behavior of E. coli O157:H7, providing a theoretical basis for the prevention and control of biological contamination in wastewater treatment processes. Graphical abstract: Image 1 Highlights：: It is the first time to study the survival of E. coli O157:H7 in CWs. The survival time of E. coli O157:H7 is longer in H-CW than in L-CW. NH4 + -N and AP essentially impact the survival of E. coli O157:H7 in CWs. Specific keystone taxa regulate the survival of E. coli O157:H7 in CWs. The biotic properties more affect the survival of E. coli O157:H7 in CWs.